Synthesis, characterization and thermal degradation of poly[(2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate] - Coskun, M; Ilter, Z; Ozdemir, E; Demirelli, K; Ahmedzade, M (Elsevier Sci Ltd, 1998)
(2-Phenyl-1,3-dioxolane-4-yl)methyl methacrylate prepared from glycidyl methacrylate and benzaldehyde has been polymerized by benzoyl peroxide. Spectroscopic characterization of the monomer and the polymer has been done by means of Fourier transform infra-red (FTIR) and H-1 and C-13 nuclear magnetic resonance (NMR) spectroscopies. Also, the techniques of gel permeation chromatography and differential scanning calorimetry have been used in the polymer characterization. Thermal degradation of poly[2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate] has been studied by thermogravimetric analysis and FTIR. Volatile products of the degradation have been investigated by FTIR, H-1 and C-13-NMR and gas chromatography-mass spectrometry techniques. The degradation to 270 degrees C of this polymer gives only the monomer. Side-chain decompositions mainly occur in degradation above 270 degrees C, including decomposition of the 1,3-dioxolane ring. Total degradation to 500 degrees C produces many volatile product such as the monomer, benzaldehyde, acrolein, acetone, 2-phenyl-4-hydroxymethyl-1,3-dioxolane, 4-methylene-2-phenyl-1,3-dioxolane, propane, carbon dioxide and others. A mechanism of degradation showing the formation of some of these products is discussed. (C) 1998 Elsevier Science Limited. All rights reserved.